Six dimensions of public law: pressure-testing the UK and EU system - Craig, P (Oxford University Press, 2020)
This chapter draws on the six dimensions of public law covered in the book: theory, institutions and accountability, constitutions and rights, process and procedure, legislation, and case law. It links discussion of these dimensions, by considering how they have been affected by Brexit. The chapter is not concerned with the contending arguments for leaving or remaining in the European Union. The focus is on the way in which Brexit has ‘pressure-tested’ the public law regime in the United Kingdom and the European Union. The six dimensions of public law that are discussed in the preceding chapters form the architectural frame through which the impact of Brexit on the public law regimes is assessed in both the United Kingdom and the European Union.